Refleksi Aksiologi atas Nilai-Nilai Pendidikan Karakter pada Tradisi Keleleng di Desa Punggur Kecil: Refleksi Aksiologi atas Nilai-Nilai Pendidikan Karakter pada Tradisi Keleleng di Desa Punggur Kecil - Saripaini, Saripaini (Perkumpulan Sarjana Pendidikan Islam Indonesia (PSPII) Wilayah Kalimantan Barat, 2021)
This article aims to review the value and benefits of the Keleleng tradition in the Punggur Kecil Village community's farming system, Kubu Raya Regency, West Kalimantan. This study uses an axiological approach to reveal how existing values ​​can regulate the bonding of society to one another so as to create brotherhood. This research is descriptive qualitative research using a literature review combination reinforced by observations of field life and a series of interviews. Data were collected through literature collection and field observations. The data obtained are described accordingly. The activities carried out in the data analysis process, namely: data collection, data reduction, data display, and drawing conclusions. The results showed that there are local wisdom values ​​contained in the tradition of keleleng in Punggur Kecil Village, Kubu Raya Regency, West Kalimantan Province, namely: the value of discipline and responsibility, the value of cooperation, the value of kinship, the value of caring, the value of generosity, the value of leadership. These seven values ​​become ethics and aesthetics formed in the social system so that there is a closeness between the local people.